Current trends in dental implant practice among dentists in Nepal - Vaidya, S; Rajkarnikar, J; Rana, SB; Bhochhibhoya, A; Khapung, A (Journal of Nepalese Prosthodontic Society, 2021)
Introduction: Implant dentistry is one of the fastest growing specialty in the field in dentistry. Yet there is a paucity of literature regarding the prevalence and the current trends of implant dentistry practice among dentists working in Nepal. Thus, the objective of this study was to assess the prevalence and current trends of dental implants practice among the dentists working in Nepal. Method: A cross sectional, online study was done among 267 Nepalese dentists from October, 2020 to December, 2020 by convenience sampling method. Data collection was done with the help of a proforma that included socio-demographic details and predesigned questionnaire adopted from a study done in Mumbai, India.13 The questions were developed in google form and shared to the study participants through various social media for the study duration of 3 months. Results: Out of 267 participants, 142 (53.2%) were BDS, 107 (40.1%) were MDS and remaining had other degrees. Of the total participants, only 83 (31.1%) placed dental implants in their practice. Those who did not place dental implants referred the case mostly to periodontist (51.1%), followed by prosthodontist (34.8%). Only 72 (26.9%) had undergone formal implant training program. All the study participants prescribed radiograph as CBCT alone or in combination with the other radiographs. Most of the participants, who placed dental implant, did both the surgical and the prosthodontic phases. Bone level implants (74.7%), Screw retained (50.6%) and extra oral fixation (50.6%) type prosthetics were used by most of the participants. Most frequently used implant systems were Bredent (46.9%), Nobel Biocare (46.9%) and Straumann (46.9%) followed by Adin (44.5%). Conclusion: The current study showed that dental implants practice is adopted by less than one third of the dentists in Nepal, that suggests the need for implementation of Continuing Professional Development in dental implants in Nepal to increase the knowledge and skills among dental professionals.